LEGAL CHALLENGES IN COVER SONG DISPUTES: A CIVIL PROCEDURAL PERSPECTIVE ON COPYRIGHT ENFORCEMENT - Sari, Dewi Arnita; Hanani, Azka (Jurnal Al-Dustur, 2025)
Cover song disputes have emerged as a significant concern within civil procedural law in the digital age, driven by the proliferation of online music platforms and frequent disregard of copyright compliance. This study aims to investigate the challenges faced by artists in understanding and adhering to song cover copyright regulations. Employing a qualitative methodology, the research gathered data through in-depth interviews with 50 purposively selected respondents, including musicians, producers, and legal professionals within the music industry. Thematic analysis was used to identify key patterns and themes, revealing that 60% of artists lacked awareness of the legal requirements for obtaining permission to create song covers, leading to increased legal uncertainty and disputes over intellectual property. These findings highlight the critical need for comprehensive educational initiatives and clearer regulatory frameworks to address this knowledge gap and support compliance. Enhancing copyright literacy among artists is essential to fostering a legally secure and balanced environment in the music industry. This study contributes to the existing literature on copyright challenges in the arts sector and underscores the urgent need for regulatory updates and practical measures to ensure fair use and protection of creators' rights in an increasingly digital music ecosystem. Future research should explore the dynamic interaction between evolving technologies and copyright law in shaping the practices of artists and the broader music industry, ensuring the sustainability and fairness of the creative economy.Top of Form